A ''naked-eye'' colorimetric and ratiometric fluorescence probe for trace hydrazine. Issue 19 (7th May 2019) - Wu, Cuiyan; Xu, Hai; Li, Yaqian; Xie, Ruihua; Li, Peijuan; Pang, Xiao; Zhou, Zile; Li, Haitao; Zhang, Youyu
Abstract : A new colorimetric and ratiometric fluorescence probe was developed for detection of hydrazine (N2 H4 ) based on the mechanism of intramolecular proton transfer excited state (ESIPT). Abstract : Hydrazine (N2 H4 ) is widely used in industry but also very toxic. Herein, we describe the preparation of a ''naked-eye'' colorimetric and ratiometric fluorescent probe (DH ), bearing α, β-unsaturation carbonyl group as a recognition site, and employ it for the excited-state intramolecular proton transfer based (ESIPT-based) detection of N2 H4 . The probe can detect N2 H4 by colorimetric and ratiometric fluorescence dual signals with high sensitivity and selectivity; the detection limit of N2 H4 was 0.063 μM (2.01 ppb), which was far below the safety level (10 ppb) stated by the U.S. Environmental Protection Agency (EPA). It enables "naked-eye" detection for hydrazine determination in aqueous solution. More importantly, we successfully appliedDH to detect N2 H4 in real water samples, indicating its potential utility for N2 H4 sensing in environmental samples.